Comprehensive Study of Hṛdaya Marma with Special Reference to the Applied Aspect of the Heart (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
In Ayurveda, Marma refers to vital points where prāṇa (life force) is concentrated. Among the 107 Marma points, Hṛdaya Marma holds the highest significance, as it governs life (Jeevana) [1]. Understanding Hṛdaya Marma offers valuable insights into Ayurvedic physiology and pathology, correlating with modern cardiac anatomy and function. This study explores Hṛdaya Marma from both perspectives, emphasizing its clinical relevance in cardiovascular health.